Integrasi Nilai-Nilai Islam dalam Praksis Manajemen Guru dan Self-Regulated Learning Siswa di MTs Muhammadiyah Blimbing - '`Ainina, Mutanafisah Qurrotu; Soleh, Mad; Suharto, Toto; Muharom, Fauzi (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2025)
This study examines the contribution of systematic classroom management and the integration of Islamic values to the development of self-regulated learning (SRL) in Madrasah Tsanawiyah students. The study was conducted using a qualitative approach based on literature review, enriched with semi-structured interviews with a teacher at MTs Muhammadiyah Blimbing in November 2025 to provide an empirical picture of field practices. The analysis results indicate that proactive classroom management—including the formulation of learning objectives, orderly transition arrangements, provision of formative feedback, and reflective closures support the development of forethought, monitoring, and self-evaluation processes in learning strategies. Islamic values such as amanah (trustworthiness), discipline, and muhasabah (self-reflection) strengthen autonomous motivation so that students understand the meaning of learning activities and feel responsible for their tasks. The integration of pedagogical structure and value orientation fosters SRL as a habitual learning practice. Practically, research recommends a structured classroom routine to strengthen autonomy while maintaining the spiritual identity of Islamic educational institutions.